Search-Based ApplicationsAt the Confluence of Search and DatabaseTechnologies - Grefenstette, Gregory (Morgan & Claypool, 2011)
What will data management technologies look like in ten years? While the future's difficult to predict, this book provides students, researchers and professionals alike with a brief and engaging look at one prescient trend: the convergence of search and database technologies. This convergence has given rise to a new breed of non-relational ('NoSQL') databases and data stores, and to a new generation of search engines that share characteristics with both non-relational and relational databases. It is this new type of engine that supports Search Based Applications (SBAs), which are software applications built on a search rather than database backbone. SBAs offer a pragmatic way to solve both well-known and emerging information management challenges as of now, while shedding light on what tomorrow's information systems might look like.